The outcome of facial nerve decompression via transmastoid approach in facial palsy secondary to the temporal bone fracture - Raja Lope Ahmad, Raja Ahmad Al'konee; Wan Leman, Wan Ishlah; Abdullah, Kahairi; Md Ralib @ Md Raghib, Ahmad Razali; Kamarudin, Norie Azilah (2007)
OBJECTIVES: The aim of this study is to analyze the outcome of surgical management in traumatic facial paralysis secondary to temporal bone fracture.